From Traditional Resource to Global Commodities:—A Comparison of Rhodiola Species Using NMR Spectroscopy—Metabolomics and HPTLC - Booker, Anthony; Zhai, Lixiang; Gkouva, Christina; Li, Shuyuan; Heinrich, Michael (Frontiers in Pharmacology, 2016)
The fast developing international trade of products based on traditional knowledge and their value chains has become an important aspect of the ethnopharmacological debate. The structure and diversity of value chains and their impact on the phytochemical composition of herbal medicinal products has been overlooked in the debate about quality problems in transnational trade. Different government policies and regulations governing trade in herbal medicinal products impact on such value chains. Medicinal Rhodiola species, including Rhodiola rosea L. and Rhodiola crenulata (Hook.f. & Thomson) H.Ohba, have been used widely in Europe and Asia as traditional herbal medicines with numerous claims for their therapeutic effects. Faced with resource depletion and environment destruction, R. rosea and R. crenulata are becoming endangered, making them more economically valuable to collectors and middlemen, and also increasing the risk of adulteration and low quality. We compare the phytochemical differences among Rhodiola raw materials available on the market to provide a practical method for Rhodiola authentication and the detection of potential adulterant compounds. Samples were collected from Europe and Asia and nuclear magnetic resonance spectroscopy coupled with multivariate analysis software and high performance thin layer chromatography techniques were used to analyse the samples. A method was developed to quantify the amount of adulterant species contained within mixtures. We compared the phytochemical composition of collected Rhodiola samples to authenticated samples. Rosavin and rosarin were mainly present in R. rosea whereas crenulatin was only present in R. crenulata. 30% of the Rhodiola samples purchased from the Chinese market were adulterated by other Rhodiola spp. Moreover, 7 % of the raw-material samples were not labelled satifactorily. The utilisation of both 1H-NMR and HPTLC methods provided an integrated analysis of the phytochemical differences and novel identification method for R. rosea and R. crenulata. Using 1H-NMR spectroscopy it was possible to quantify the presence of R. crenulata in admixtures with R. rosea. This quantitative technique could be used in the future to assess a variety of herbal drugs and products. This project also highlights the need to further study the links between producers and consumers in national and trans-national trade.